A huge adenosquamous carcinoma of the pancreas with sarcomatoid change: An unusual case report - Lu, Bao-Chun (World J Gastroenterol, 2014)
Adenosquamous carcinoma rarely occurs in the pancreas, and is characterized by the presence of cellular components from both duct adenocarcinoma and squamous carcinoma. Here, we describe a rare case of pancreatic adenosquamous carcinoma with sarcomatous change. Immunohistochemistry showed that the sarcomatous lesion lost the epithelial marker and aberrantly expressed of acquired mesenchymal markers, which indicated that this special histological phenotype may be attributed to epithelial-mesenchymal transition. This case also indicated that a routine radical surgery without aggressive treatment strategies was still appropriate for adenosquamous carcinoma of the pancreas with sarcomatoid change.